Eksperimentasi Pembelajaran Fisika Melalui Pendekatan Lingkungan Alam Sekitar dan Pendekatan Konvensional di Tinjau dari Hasil Belajar Siswa - Fahima Muhlis; Nursanti Ali (Peneliti.net, 2020)
This study aims to improve student learning outcomes by using the Natural Environment Approach. The research method is quantitative research with this type of research is the type of research used is comparative while the research design is a control group pretest-posttest design. Based on the discussion of the results of research in class XI SMA Negeri 8 Tikep, it can be concluded that the use of the Natural Environment Approach can significantly improve student learning outcomes compared to learning using a conventional approach. Statistically tested with t value of 3.742> 2.014 ttable value so that H0 is rejected and H1 is accepted, which means an increase in learning outcomes using the Approach of the Natural Environment. The magnitude of the increase in learning outcomes can be seen in the post-test average score of 58.90 in the control class and 79.56 in the experiment. Therefore. From the SPSS output, it is known that